2013
DOI: 10.1016/j.neurobiolaging.2012.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid deposition detected with florbetapir F 18 (18F-AV-45) is related to lower episodic memory performance in clinically normal older individuals

Abstract: The objective of this study was to evaluate the relationship of amyloid burden, as assessed by florbetapir F 18 (18F-AV-45) amyloid PET, and cognition in healthy older control subjects (HC). Seventy-eight HC subjects were assessed with a brief cognitive test battery and PET imaging with florbetapir F 18. A standard uptake value ratio (SUVr) was computed for mean data from six cortical regions using a whole cerebellum reference region. Scans were also visually rated as amyloid positive (Aβ+) or amyloid negative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

11
83
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 119 publications
(96 citation statements)
references
References 48 publications
(75 reference statements)
11
83
2
Order By: Relevance
“…Our findings have also confirmed the selective impairment of cognitive domains involved in the amyloid-cognition relationship. Episodic memory decline associated with amyloid burden appears earlier than other cognitive domain declines, 12,20,23 and cognitive declines in global cognition and working memory occur in symptomatic stages. 17,19,23 In our current findings examining s-MCs, amyloid PET was associated with cross-sectional deficits but not longitudinal declines in episodic memory, a finding at odds with some studies of late-onset symptomatic AD.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Our findings have also confirmed the selective impairment of cognitive domains involved in the amyloid-cognition relationship. Episodic memory decline associated with amyloid burden appears earlier than other cognitive domain declines, 12,20,23 and cognitive declines in global cognition and working memory occur in symptomatic stages. 17,19,23 In our current findings examining s-MCs, amyloid PET was associated with cross-sectional deficits but not longitudinal declines in episodic memory, a finding at odds with some studies of late-onset symptomatic AD.…”
Section: Discussionmentioning
confidence: 95%
“…Most prior studies of cognitively healthy older people demonstrated episodic memory decline associated with amyloid burden in the brain 7,[10][11][12][13]15,18,20,21,23 earlier than other cognitive domain declines. 12,20,23 A meta-analysis including 16 independent cohorts (maximum of 1,278 participants) assessed the amyloid-cognition relationship in cognitively normal adults, and the results also showed that only episodic memory had a modest but significant negative relationship to amyloid burden detected by PiB-PET in presymptomatic AD. 39 Similar to these results found in sporadic AD, our results in ADAD showed that cerebral amyloidosis predicted episodic memory decline over time in presymptomatic ADAD.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In addition, discrepant data exist regarding the relationships between amyloidosis or neurodegeneration and cognitive decline in preclinical AD. 3,5 Neurodegeneration can be measured using the hippocampal volume or cortical thickness within the topography affected by AD (i.e., "AD signature"). 6,7 The AD signature has been shown to predict prognosis in individuals without dementia, 8 although an important gap remains.…”
mentioning
confidence: 99%
“…1,2 CN subjects [3][4][5] and subjects with MCI 6,7 who are amyloid-positive experience greater cognitive decline than amyloid-negative individuals. Amyloid positivity must therefore be recognized as a pathologic state.…”
mentioning
confidence: 99%